The Biologic and Economic Effect of Introducing Poultry Waste in Rabbit Diets - Owen, O.J.; Amakiri, A.O.; Ngodigha, E.M.; Chukuigwe, E.C. (International Journal of Poultry Science, 2008)
A 12 week feeding trial was conducted using 24 (2-3 months-old) Chinchilla rabbits to assess the economic effect of substituting poultry litter (PL) for soy bean meal (SBM). Soy bean meal in the diets was replaced with poultry litter at 0% (Diet A-control), 5% (Diet B), 10% (Diet C) and 15% (Diet D). The rabbits were divided into four groups; each group was assigned to one of the four dietary treatments in a Completely Randomized Block Design (CRBD). Each treatment was replicated three times. The economics of production indicated a better performance in poultry litter substituted diets over the control group in all the indices vis-à-vis cost/kg feed (), cost/kg weight gain, cost of weight gain () and relative cost (%) measured suggesting that poultry litter has an economic advantage over soy bean meal as protein supplement in ration formulation.